Assessing the Impact of an Intervention Project by the Young women's Christian Association of Malawi on Psychosocial Well-Being of Adolescent Mothers and Their Children in Malawi - Kachingwe, Mtisunge; Chikowe, Ibrahim; van der Haar, Lotte; Dzabala, Nettie (Frontiers in Public Health, 2021)
Adolescent mothers in Malawi face psychosocial challenges such as low resilience level, low self-esteem, poor maternal-infant interaction, and exposure to intimate partner violence (IPV). Children of adolescent mothers often face numerous risks such as low birth-weight, stunted growth, infant death, low school enrolment, increased grade repetition, and dropouts that put them at greater risk of poor developmental outcomes and socio-emotional problems. This study assessed the impact of components of a community project conducted by the Young Women's Christian association of Malawi in providing psychosocial support to adolescent mothers and their children. The goals of the project were; (1) to improve early childhood development in babies born to adolescent mothers; and (2) to enhance the psychosocial well-being of adolescent mothers (self-esteem, resilience stress, and parenting skills). This descriptive mixed methods evaluation study comprised an intervention and control groups of adolescent mothers respectively. The project had 3 centers in southern region districts of Malawi. Target population was adolescent mothers 18 years of age and below. At baseline we enrolled 267 mothers and at the end of the project we had 211 mothers. The project involved monthly meetings with adolescent mothers imparting knowledge and skills and early childhood education activities. From July 2017 to June 2019, 58 sessions were conducted. In the first year the control group had no meetings, however they received the intervention in the second year. Overall results in the intervention group showed statistically significant increase in knowledge on parenting skills (p < 0.01), nutritional practice (p < 0.01), motor skills and cognitive functions in children (p < 0.01) as well as expressive language and socio-emotional capacities in children (p < 0.01), while the change in confidence and psychosocial well-being was not statistically significant (p = 0.8823). Community projects such as these enhance parenting skills and improve development of children born to adolescent mothers. Improving psychosocial support is complex and requires further research and a more holistic approach.